2009
DOI: 10.1007/978-3-642-02771-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-photorealistic 3D Urban Models for Mobile Device Navigation

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Abstract. This research presents a user evaluation study examining the effect different rendering styles of 3D virtual city models, as intended for navigational purposes, could potentially have on users with emphasis on non-photorealistically rendered (NPR) stylizations. The purpose of this experiment is to establish whether, particularly for the application area mentioned above, non-photor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1. Automatic modelling (Figure 12): 3D simulation of architectural/urban models and automatic digital design and simulation via VHF wireless devices [90], automation of modelling based on spatial photographs, aerial photographs, and georeferenced images [5], either through accurate photogrammetric methods [97] or with special applications based on algorithms that generate photorealistic images [98].…”
Section: Research and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Automatic modelling (Figure 12): 3D simulation of architectural/urban models and automatic digital design and simulation via VHF wireless devices [90], automation of modelling based on spatial photographs, aerial photographs, and georeferenced images [5], either through accurate photogrammetric methods [97] or with special applications based on algorithms that generate photorealistic images [98].…”
Section: Research and Perspectivesmentioning
confidence: 99%
“…Fig. 12 Examples of automatic modelling: a) Automated remote modelling process [96]; b) Photo-based, "virtual city maker" [98]; c) Photo-based capture [99]; d) Based on photos [100] 2. Mobile simulation: export of 3D interactive architectural/urban environment to mobile devices (mobile phones, tablets, watches, GPS, etc.)…”
Section: Research and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Popelka and Doležalová (2016) also examined nonphotorealistic visualization of cities, specifically dealing with static perspective bird-eye views and their comparison with 2D maps using eye tracking. Recommendations regarding photorealistic visualization are formulated by Gatzidis et al (2009). They identified that non-photorealistic shading and especially expressive rendering could provide more effective visual styles than photorealistic representations of built-up areas.…”
Section: User Testing Of 3d City Modelsmentioning
confidence: 99%